Cochlear Synaptopathy due to Mutations in OTOF Gene May Result in Stable Mild Hearing Loss and Severe Impairment of Speech Perception. Issue 6 (November 2021) - Santarelli, Rosamaria; Scimemi, Pietro; Costantini, Marco; Domínguez-Ruiz, María; Rodríguez-Ballesteros, Montserrat; del Castillo, Ignacio
Abstract : Objectives: Congenital profound hearing loss with preserved cochlear outer hair cell activity (otoacoustic emissions and cochlear microphonic) is the most common phenotype associated with mutations in the OTOF gene. The aim of this study was to investigate the pathophysiological mechanisms behind the auditory dysfunction in five patients (2 adults and 3 children) carrying biallelic mutations in OTOF, who showed an uncommon phenotype of mild hearing impairment associated with severe difficulties in speech perception and delay of language development. Design: Patients underwent audiometric assessment with pure-tone and speech perception evaluation, and otoacoustic emissions and auditory brainstem response recording. Cochlear potentials were recorded in all subjects through transtympanic electrocochleography in response to clicks delivered in the free field from 120 to 60 dB peak equivalent SPL and were compared to recordings obtained from 20 normally hearing controls and from eight children with profound deafness due to mutations in the OTOF gene. Three patients out of five underwent unilateral cochlear implantation. Speech perception measures and electrically evoked auditory nerve potentials were obtained within 1 year of cochlear implant use. Results: Pathogenic mutations in the two alleles of OTOF were found in all five patients, and five novel mutations were identified. Hearing thresholds indicated mild hearing loss in four patients and moderate hearing loss in one. Distortion product otoacoustic emissions were recorded in all subjects, whereas auditory brainstem responses were absent in all but two patients, who showed a delayed wave V in one ear. In electrocochleography recordings, cochlear microphonics and summating potentials showed normal latency and peak amplitude, consistently with preservation of both outer and inner hair cell activity. In contrast, the neural compound action potential recorded in normally hearing controls was replaced by a prolonged, low-amplitude negative response. No differences in cochlear potentials were found between OTOF subjects showing mild or profound hearing loss. Electrical stimulation through the cochlear implant improved speech perception and restored synchronized auditory nerve responses in all cochlear implant recipients. Conclusions: These findings indicate that disordered synchrony in auditory fiber activity underlies the impairment of speech perception in patients carrying biallelic mutations in OTOF gene who show a stable phenotype of mild hearing loss. Abnormal nerve synchrony with preservation of hearing sensitivity is consistent with selective impairment of vesicle replenishment at the ribbon synapses with relative preservation of synaptic exocytosis. Cochlear implants are effective in restoring speech perception and synchronous activation of the auditory pathway by directly stimulating auditory fibers.